Name ___________________________________________

### SIMPLIFY. Connect the answers in order.

Start a new line.
1. - 6(5) - 3(- 2x - 6) = 6x - 12
2. - 6(4x - 5) - 6(- 5x + 4) = 6x + 6
3. 4(- 6x-1) + 3(- 3x - 5) = - 33x -19
4. - 2(- 2x - 3) - 2(- 3) = 4x + 12
5. 3(- 6x - 4) = - 18x - 12
6. (2x + 2) + 2(x + 5) = 4x + 12
7. - (- 4) - 4(- 2x + 3) = 8x - 8
8. - 4(- x + 2) + 2(- 2x + 5) = 2
9. - 6(x - 4) - (- 6x + 1) = 23
10. 3(2) + 2(2x - 6) = 4x - 6
11. - 12x + 4 +2(- 2x + 2) = - 16x + 8
12. 2(- 6x) + 4(- 2x + 5) = - 20x + 20
13. - 8(x + 2) -(10x - 4) = - 18x - 12
14. 2(- 10x - 10) = - 20x + 20
15. - 20x + 4x + 3 + 5 = - 16x + 8
16. 5(2x + 3) - 6x - 21 = 4x - 6
17. 2(3x - 4) = 6x - 8
18. 5(- 3x + 4) + 4(4x - 6) = x - 4
19. 5(- 6x - 6) + 5(2x) = -20x - 30
20. 4(x+ 1) - 3x - 8 = x - 4
21. - 2(- 4x) - 2(3x + 1) = 2x - 2
22. 5x + 4 - 5x - 1 = 3
23. - 3(- x- 2) - 6(3x + 1) = - 15x
24. 2(- 4x -3) - 3(4x - 3) = - 20x + 3
25. -3(5x +1) +3 = - 15x
26. 3( - 2x + 1) + 3(2x -1) = 0
27. 5(- x + 5) + 4(2x - 6) = 3x + 1
28. - 2(4x - 3) + 2(- 4x - 3) = -16x
29. 5(1) + 2(2x + 5) = 4x + 15
30. 4(x - 4) = 4x -16
31. - 2(5x + 2) - 5(4x) = - 30x - 4
32. 3(- 6x + 4) + 4(- 3x - 6)
= - 30x -12
33. - 5(4) - 4(5x + 1) = - 20x - 24
34. 9 - 4x + 4x = 9
35. - 2(- 5x + 5) - 1(x - 6) = 9x - 4
36. - 4(x - 1) - 4( - x - 1) = 8
37. -5x - 5 + 4(- 6x -1) = - 29x - 9
38. 5(x + 3) - (5x + 7) = 8
39. 4(- 2x) = - 8x
40. - 2(4x - 2) = - 8x + 4
41. 1(- 5) - 4(x - 2) = - 4x + 3
42. - 2(4x) + 3(x - 4) = - 5x -12
43. - 3(5x -6) - 6(- 2x + 2) = - 3x + 6
44. - 4(4x - 6) - 5(- 2) = - 16x + 34
45. 2(2x + 4) + 2(- 5x + 3) = - 6x + 14
46. - 1(- 2x - 6) - 2(4x - 1) = - 6x + 8
47. 5(x - 6) - 3(3x + 3) = - 4x - 39
48. -2(x - 4) - 4x = - 6x + 8
49. - 3(3x + 1) + 4(- 3x - 6)
= - 21x -27
50. 5x - 3 + 2(- 4x + 5) = - 3x + 7
51. - 2(- 6x - 2) - (4x - 4) = 8x + 8
52. - 5(-3) + 4(2x) = 8x + 15
53. 5(- 4x + 1) + 2(- 5x - 1) = - 30x + 3
54. - (3x + 10) - (x + 29) = - 4x - 39
Start a new line!
55. - 2(- 5x -1) + 2(x - 6)
= 12x - 10
56. 3(5x + 3) = 15x + 9
57. - 4(2x+5)+5(-4x-3)
= -28x-35
58. 5(5x + 1) - 5(2x - 5)
= 15x + 30
59. 5(- x - 1) - 4(- 2x - 4)
= 3x + 11
60. - 5(-3x+4)-3(2x-6)
= 9x - 2
61. - 3(- 4x + 1) = 12x - 3
62. - 4(3x-4)+2(-3x-3)
= -18x + 10
63. - 6(2x-4)-5(-5x-3)
= 13x + 39
64. 4(3x+2)-1(-5)
= 12x + 13
65. 3x-3+2(4x-6)
= 11x - 15
66. -(4x-6)+5(3x-3)
= 11x - 9